2021
DOI: 10.1155/2021/5019481
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Edaphic Drivers of Yam Production in West Africa

Abstract: Yam is an important food and cash crop in West Africa (the yam belt) whose production is traditionally nonsedentary due to its substantial nutrient demand. Population growth, urbanization, and existing soil degradation have made nonsedentary farming virtually impossible. Despite the numerous research invested in yam production within and outside the yam belt, some gaps remain to be filled owing to changing climate events and global developments. Alarmingly, the yam belt is facing sharp yield declines despite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…First, D. alata is an important traditional food crop and considered a rich source of carbohydrates (75–84%), proteins (~7.4%), and vitamin C (13.0–24.7 mg/100 g) [ 4 , 5 ]. Second, D. alata has sufficient capacity to adapt to diverse agro-ecological and climatic environments and can be easily propagated vegetatively by tuber pieces [ 6 , 7 , 8 ]. Third, its tubers often have a delicate taste, an attractive tuber appearance, and an excellent long-term (4–6 months) storage ability [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, D. alata is an important traditional food crop and considered a rich source of carbohydrates (75–84%), proteins (~7.4%), and vitamin C (13.0–24.7 mg/100 g) [ 4 , 5 ]. Second, D. alata has sufficient capacity to adapt to diverse agro-ecological and climatic environments and can be easily propagated vegetatively by tuber pieces [ 6 , 7 , 8 ]. Third, its tubers often have a delicate taste, an attractive tuber appearance, and an excellent long-term (4–6 months) storage ability [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among various tuber and root crops, yam ( Dioscorea rotundata and D. alata) is extremely valuable in West Africa, impacting the economic fate of millions of smallholder farmers 10 – 14 . Various climatic, cultural and edaphic factors dictate yam crop yield and quality 11 ; more importantly, 17–50% of the crop is lost annually to plant-parasitic nematodes (PPNs) 13 , 15 – 17 .…”
Section: Mainmentioning
confidence: 99%
“…), yam ( Scutellonema bradys ) and lesion ( Pratylenchus spp.) 13 , 14 , 18 , play major roles in reducing yam crop values primarily because of lack of available, affordable control options 6 , 9 , 11 . The yam nematode S. bradys is probably the single-most important parasite due to its ubiquitous presence in yam plantings 14 .…”
Section: Mainmentioning
confidence: 99%
“…(2010) reported that about 400 million people thrive on yam as their main food source. About 72.58 million metric tons of yam are produced globally with major producers being Nigeria (73%), Ghana (12.5%), Côte d’Ivoire (10.5%), and Benin (4.5%) ( Neina, 2021 ). They are good source of carbohydrate, and provides about 200 calories of energy per capita on daily consumption ( Okoro and Ajieh, 2014 ).…”
Section: Introductionmentioning
confidence: 99%